"مساهمة التحفيز المعنوي للعاملين في تطوير جودة الخدمة (دراسة حالة مؤسسة اتصالات الجزائر بالوادي) " - العلمي, مصباحي; عبد السلام, رويحة (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى معرفة مدى مساهمة التحفيز المعنوي للعاملين في تطوير جودة الخدمة بمؤسسة اتصالات الجزائر فرع الوادي، ولتحقيق أهداف الدراسة تم الاعتماد على استبيان مكون من 40 فقرة يشتمل على شق خاص بالمتغير المستقل (التحفيز المعنوي للعاملين)، وشق آخر يخص (جودة الخدمة) وابعادها المتمثلة في (الملموسية، الاعتمادية، الاستجابة، الأمان، التعاطف). وقد اشتملت عينة الدراسة على 37عامل بالمؤسسة محل الدراسة، واعتمدنا في تحليل بيانات الاستبيان على برنامج spss. وأظهرت نتائج الدراسة ما يلي: - أظهرت الدراسة أن مستوى التحفيز المعنوي السائد في مؤسسة اتصالات الجزائر فرع الوادي جاء متوسطا، وأن مستوى جودة الخدمة بالمؤسسة اتصالات الجزائر فرع الوادي جاء مرتفعا وفق المقياس الدراسة. - يوجد دور ذو دلالة معنوية التحفيز المعنوي في تحسين جودة الخدمة بالمؤسسة اتصالات الجزائر فرع الواديعند مستوى دلالة (α=0.05). - يوجد دور ذو دلالة معنوية التحفيز المعنوي في تحسين الاعتمادية في مؤسسة اتصالات الجزائر فرع الواديعند مستوى دلالة (α=0.05). - يوجد دور ذو دلالة معنوية التحفيز المعنوي في تحسين التعاطف في مؤسسة اتصالات الجزائر فرع الوادي عند مستوى دلالة (α=0.05). ""This study aims to find out the extent to which the moral motivation of the workers contributes to the development of service quality in the Algerian Telecom Corporation, the Valley Branch, and in order to achieve the objectives of the study, a 40-paragraph questionnaire was adopted that includes a section for the independent variable (moral motivation for workers), and another part for (service quality) And its dimensions represented in (tangibility, reliability, responsiveness, safety, and empathy(. The study sample included 37 workers in the institution under study, and we relied on the analysis of the questionnaire data on the spss program. The results of the study showed the following: - The study showed that the level of moral motivation prevailing in Algeria Telecom, Wadi Branch, was medium, and that the level of service quality in Algeria Telecom, Wadi Branch, was high according to the study scale. - There is a significant role for moral stimulation in improving the quality of service at the Algeria Telecom Corporation, El Wadi Branch, at a significance level (α = 0.05). - There is a significant role for moral stimulation in improving reliability in Algeria Telecom El Oued Branch at significance level (α = 0.05). - There is a significant role for moral stimulation in improving empathy in Algeria Telecom El Wadi Branch at a significance level (α = 0.05). "
مذكرة ماستر ادارة اعمال
Keywords: تحفيز معنوي للعاملين، جودة الخدمة، أبعاد جودة الخدمة، مؤسسة اتصالات.; Moral motivation for workers, service quality, dimensions of service quality, telecommunications institution.